Formation of Linguistic Competencies in Teaching Paronymous Words Given in Mother Language and Reading Literacy Textbook - Makhmudova Sadokat Kholmatovna; Latipova Shahrinoz Bobirovna (Zien Journals, 2023)
Enriching the vocabulary of elementary school students with paronyms practical issues of formation of speech competences the issues of appropriate use of paronymous words in the speech process are covered.
Keywords: Competence; paronyms; language; pronunciation